Acid resistance of goethite in nickel laterite ore from Western Australia. Part II. Effect of liberating cementations on acid leaching performance - Wang, Xiaodong; McDonald, R.; Hart, Robert; Li, J.; van Riessen, Arie (Elsevier Science BV, 2014)
The acid resistance of some West Australian laterite ores has been reported to be associated with its cementation structure at submicron level. Although closely related, iron and silicon are found not to be intimately mixed in the goethite-silica/silicate cementations from the current Energy Filtered Transmission Electron Microscopy examination. The round or diamond tips of the liberated goethite crystals suggest slow crystal growth in high silicate conditions. The effect of pre-treating the cementation structure by potassium hydroxide liquor digestion upon the atmospheric pressure acid leaching performance is also studied in this paper. Both particle size analysis using laser diffraction and direct imaging using Transmission Electron Microscopy confirm the effective disintegration of the cementations and the liberation of goethite crystals. As a result, the leaching rates of these nickel laterite ores increase by more than 6 times; nickel recoveries of these laterite ores are also increased from under 50% to near 90% after 16 h acid leaching. The accelerating effect of the potassium hydroxide pre-treatment upon acid leaching rates verified that an envelope of silica and/or silicates hindered the contact between acid and goethite crystals during atmospheric leaching of these nickel laterite ores.